PERAN KEPEMIMPINAN DAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN OKU - Yuniarni, Elsa; Efrianti, Rini; Oktarina, Yetty; Sari, Yunita (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
Leadership is a consistent pattern of behavior used by a leader to influence their subordinates or team members, as well as the additional influence that exceeds and goes beyond the mechanical needs in routinely directing the organization. Discipline is the management action to encourage its members to comply with existing regulations in the company, such as working hours, dress code, use of equipment, office supplies, and so on. This research will be intentionally conducted (Purposive) at the Communication and Information Office of OKU Regency. The sampling method used in this study is the census method, where the number of employees at the Communication and Information Office in OKU Regency is a total of 41 civil servants. The data processing method will involve a series of steps to manage, analyze, and interpret the collected data, using linear regression analysis. Based on the analysis and discussion presented earlier, it can be concluded that the variable of leadership role (X1) and work discipline (X2) have an effect on Employee Performance (Y) at the Communication and Informatics Office of Ogan Komering Ulu Regency. It is also known that simultaneously, the variables of leadership role (X1) and work discipline (X2) influence Employee Performance (Y) at the Communication and Informatics Office of Ogan Komering Ulu Regency.